2016
DOI: 10.1080/19475705.2016.1199053
|View full text |Cite
|
Sign up to set email alerts
|

The use of an unmanned aerial vehicle for fracture mapping within a marble quarry (Carrara, Italy): photogrammetry and discrete fracture network modelling

Abstract: This paper describes the use of a drone in collecting data for mapping discontinuities within a marble quarry. A topographic survey was carried out in order to guarantee high spatial accuracy in the exterior orientation of images. Photos were taken close to the slopes and at different angles, depending on the orientation of the quarry walls. This approach was used to overcome the problem of shadow areas and to obtain detailed information on any feature desired. Dense 3D point clouds obtained through image proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…Finally, window sampling is a technique all fractures within a given sample area (window) are traced out either by hand, or on a computer, and the resulting traces used to calculate the fracture statistics (Pahl, 1981;Priest, 1993;Wu and D. 5 Pollard, 1995). This technique is often utilised to analyse remote-sampling data such as aerial photographs (Healy et al, 2017), Unmanned Arial Vehicle (UAV) images (Salvini et al, 2017), bathymetry (Nixon et al, 2012), or satellite imagery (Koike et al, 1998), as well as in outcrop studies (Belayneh et al, 2009). It has been suggested that a minimum of 110 fractures are sampled to be able to statistically describe the fracture network using window sampling (Zeeb et al, 2013).…”
Section: Fracture Data Collection and Analysismentioning
confidence: 99%
“…Finally, window sampling is a technique all fractures within a given sample area (window) are traced out either by hand, or on a computer, and the resulting traces used to calculate the fracture statistics (Pahl, 1981;Priest, 1993;Wu and D. 5 Pollard, 1995). This technique is often utilised to analyse remote-sampling data such as aerial photographs (Healy et al, 2017), Unmanned Arial Vehicle (UAV) images (Salvini et al, 2017), bathymetry (Nixon et al, 2012), or satellite imagery (Koike et al, 1998), as well as in outcrop studies (Belayneh et al, 2009). It has been suggested that a minimum of 110 fractures are sampled to be able to statistically describe the fracture network using window sampling (Zeeb et al, 2013).…”
Section: Fracture Data Collection and Analysismentioning
confidence: 99%
“…In the stability analysis of cliff faces, the identification of joint systems and fractures are key issues. The remote sensing techniques are capable of identifying these structural geological elements [30,37]. Novel methods and close range surveys using digital techniques include the use of thermo-camera [38], close-range photography [34,39], or TLS [40].…”
Section: Introductionmentioning
confidence: 99%
“…This is where the application of remote sensing techniques demonstrates many advantages. In the assessment of the structural geological conditions, these tools are often applied [29,41] for representing faults [37,42] or folds [43].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, a multitude of UAS applications [9] have emerged over the past five years including mine surveillance [10], slope stability assessment in mining [11], agriculture [12], infrastructure and construction work [13], archaeology [14], forestry [15], disaster monitoring [16], coastal environmental studies [17] and ground water research [18]. Digital elevation models obtained from UAS can deliver resolutions in (sub-)centimeter range, and are superior to conventional mapping techniques in terms of survey area, time, and target accessibility [19,20].…”
Section: Introductionmentioning
confidence: 99%